Effect of Sechium edule extract on blood sugar levels and pancreatic histopathology in male Rats with type II diabetes mellitus - Marti Silfia; Gusbakti Rusip; Linda Chiuma; Ade Indra Mukti; Lia Restumulia (Jurnal Teknologi Laboratorium)
Diabetes mellitus (DM) is a metabolic disorder characterized by elevated blood glucose levels (hyperglycemia) and the presence of glucose in the urine (glucosuria). The etiology of diabetes varies depending on its type, including Type 1 diabetes, which is caused by autoimmune destruction of pancreatic beta cells responsible for insulin production; Type 2 diabetes, resulting from insulin resistance; and gestational diabetes, triggered by hormonal changes during pregnancy affecting insulin sensitivity. Insulin plays a crucial role in glucose metabolism by converting glucose into glycogen for storage. This study aimed to evaluate the effect of Siamese pumpkin extract (Sechium edule) on blood glucose levels in male Wistar rats (Rattus norvegicus) with type II diabetes. A pre-test and post-test control group experimental design was employed, using 25 rats divided into five groups: a negative control group, a positive control group, and treatment groups receiving chayote extract at doses of 14 mg/kgBW, 28 mg/kgBW, and 42 mg/kgBW, respectively. Streptozotocin (STZ) was administered to induce diabetes in all groups except the negative control. Data analysis included normality tests, homogeneity tests, ANOVA, and post-hoc multiple comparison tests. The results demonstrated that Siamese pumpkin extract contains active compounds such as alkaloids, saponins, flavonoids, steroids, triterpenoids, tannins, and glycosides. Among the treatment groups, the administration of chayote extract at a dose of 42 mg/kgBW resulted in the most significant reduction in blood glucose levels compared to the lower doses. Histopathological analysis of pancreatic tissue revealed no abnormalities, necrosis, or degeneration across all treatment groups. The superior efficacy of the 42 mg/kgBW dose is attributed to the higher concentration of active compounds, enhanced glucose-lowering mechanisms, and improved systemic distribution.